Mompreneur: The Effect of Job Satisfaction on Psychological Well-Being of Mother Owning MSMEs - Krisnauli, Vallerie Waldine; Kadiyono, Anissa Lestari; Harding, Diana (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2024)
Not a few mothers who work in a formal work environment decide to quit and start a new career and become entrepreneurs, which makes them part of the phenomenon often known as